WHY IS THE MINARET SO SHORT? EVIDENCE FOR EARTHQUAKE DAMAGE ON MT ZION. (September 2015) - Zohar, Motti; Rubin, Rehav; Salamon, Amos
<x content-type="archive" xml:space="preserve">Abstract</x> On top of King David's Sepulchre at Mt Zion there is an Ottoman minaret known as al-Nabi Da'ud. Compared with other minarets in Jerusalem, al-Nabi Da'ud seems to be somewhat shorter, and has a squat-like appearance. To track why it is shorter than other minarets, we inspected written historical sources, a sequence of old drawings dated between the mid-eighteenth and mid-nineteenth centuries and analysed the minaret's metric proportions. In drawings dated to and before 1833, the minaret is portrayed much higher than in drawings and photographs dated to and after 1838. Furthermore, comparative height-diameter ratio of various parts of the minaret does not fit those of its counterpart, the al-Qal'a minaret. Thus, we suggest that the minaret was originally built higher but damaged during the 1834 earthquake, and reconstructed to a lower height sometimes afterwards.